Effect Of Nanoparticulates (Gd2o3, Eu2o3, Ce2o3) Addition On Properties Of (Bi1.6 Pb 0.4)Sr2 Ca2 Cu3 O10 Ceramics Superconductors - Hosseini Ravandi, Saeedeh Sadat (2009)

(untitled)
The effects of Rare Earth oxide (M) nanoparticulates addition in (Bi1.6Pb0.4)Sr2Ca2Cu3O10 + xM with M = Gd2O3, Eu2O3, Ce2O3 and x = 0.0-0.05 system, prepared by the conventional solid state reaction method have been investigated for structural, electrical and magnetic properties. The sizes of nanoparticulates oxide are 150 nm, 4 nm and 50nm respectively for Gd2O3, Eu2O3 and Ce2O3. The samples were calcined at 800° C and 830° C for 48 hours followed by sintering at 850° C for 120 hours. The morphological appearance of the samples with Gd2O3 addition generally showed platelet-like grains with random orientations, typically of 2223 phase’s structure, and by increasing the amount of nanoparticulate the platelet tend to stick together. At high percentage of nanoparticulate addition in Gd2O3 the microstructure displayed grain size from to 1.5 μm to 10 μm and increased number of pores. The morphologies of fractured surface of pellets of specimen from x=0.00-x=0.05 Ce2O3 nanoparticulate, showed that the flaky nature of the grains gradually vanished and the edges of the grains become softer and the size of the grain changed from 10 μm to 2 μm. At x=0.03 of Eu2O3 the grain size become larger in comparison with other samples. The volume fraction of the high-TC (2223) phase for addition of Gd2O3 decreased from 89% for x=0.005 to 58% for x=0.05 and in the low- TC (2212) phase the volume increased from 3.4% to 41.2 % for x=0.005 and x=0.05, respectively. The c-axis parameter decreased from 37.1293 Å to 36.7800 Å at x=0.005 to x=0.05 for Gd2O3 addition on Bi-2223. For addition with Eu2O3, we can observe some increasing in x=0.03, from x=0.01-x=0.03 volume fractions increased from x=0.01-x=0.03 according to following percentage of 83.2% to 94.3%, respectively. The lattice parameter in the c-axis increased for x=0.00 to x=0.03 in Eu2O3 addition from 37.1264 Å to 37.1432 Å. In addition with Ce2O3 nanoparticulate in pure Bi-2223, with increasing in the amount, the volume fractions reduced from 92.67% for x=0.00 to 57% in x=0.05, the c-axis also decreased from 37.1193Å to 36.8870Å for x=0.00-0.05. The critical temperature with increasing amounts of Gd2O3 x=0.00-x=0.05 decreased from 101 K to 96 K, respectively. For samples with the addition of Eu2O3, TC decreased from 101 K to 98 K and started to increase for x=0.03 with TC =103.74 K. When Ce2O3 content was further increased, the electrical behavior started to change. The onset critical temperatures were reduced from 101 K to 93 K for x=0.00-x=0.05, respectively. Measurements of AC magnetic susceptibility as a function of temperature and AC field amplitudes have been carried out for samples containing Gd2O3 nanoparticulate at constant frequency f=333.3 Hz. It is shown that with increasing addition content from x=0.00- x=0.05, the diamagnetic onset temperature decreased from 107 K for pure sample to 97 K for Gd2O3 in last content. The analysis for comparison is based on the availability of higher percentage of the high-TC (2223) phase in the sample, the suppression degree of diamagnetic behavior with respect to AC fields; rapid or slow shift of the summit in χʹʹ (T) to lower temperature with increasing field amplitude and the sharpness of χʹ (T) for the intergranular component for the same field amplitude.